Building Employee Performance through Ethical Leadership and Organizational Culture: The Mediating Role of Employee Ethical Behavior - Nenah Sunarsih; Irmawaty Irmawaty; Andriyansah Andriyansah (International Journal of Applied Business and International Management, 2026)
Employee performance is increasingly vital for organizations in the global era. This study investigates how ethical leadership and organizational culture influence employee performance, with employee ethical behaviour serving as a mediating variable. A quantitative approach was adopted, employing a survey method. The research population included all UT employees, and a sample of 175 respondents was drawn from the UT head office, UT Bandung, Jember, and Serang. Data analysis was conducted using Structural Equation Modelling (SEM) with Smart Partial Least Squares (SmartPLS). The results reveal that organisational culture has a positive and significant impact on employee ethical behaviour, whereas ethical leadership does not have a significant effect. Both employee ethical behaviour and organisational culture are found to enhance employee performance, while ethical leadership does not show a significant contribution. Additionally, organisational culture influences employee performance both directly and indirectly through ethical behaviour, while ethical leadership lacks a significant mediating effect. This study contributes new insights to the development of social learning and social exchange-based models by highlighting employee ethical behaviour as a key mechanism that elucidates the relationships among ethical leadership, organisational culture, and employee performance.